Music by subscription
1 online resource.
Keywords: "This book breaks new ground in the social and cultural history of eighteenth-century music in Britain through the study of a hitherto neglected resource, the lists of subscribers that were attached to a wide variety of publications, including musical works. These lists shed considerable light on the nature of those who subscribed to music, including their social status, place of employment, residence, and musical interests. Through broad analysis of subscription data, the contributors reveal insights into social and economic changes during the period, and the types of music favoured by groups like music clubs, the aristocracy, the clergy, and by men and women. With chapters on female composers and listeners, music and the slave economy, musical patronage, the print trade, and nationality, this book provides innovative perspectives that enhance our understanding of music's social spheres, the emergence of music publishing, and the potential of digital musicology research"--